Host-Adaptation of Burkholderia pseudomallei Alters Metabolism and Virulence: a Global Proteome Analysis - Mariappan, V.; Vellasamy, K.M.; Vadivelu, J. (Nature Publishing Group, 2017)
Little is known about the evolution, adaptation and pathogenesis of Burkholderia pseudomallei within host during acute melioidosis infection. Melioidosis is a potential life threatening disease contracted through inhalation, ingestion, inoculation or direct entry of the organism into the blood stream via wounds or skin abrasions from contaminated soil and water. Environmental B. pseudomallei strain (Bp MARAN ), isolated during a melioidosis outbreak in Pahang, Malaysia was injected intra-peritoneally into a mouse and passaged strain was recovered from spleen (Bpmouse-adapted). A gel-based comparative proteomics profiling approach was used, to map and identify differentially expressed proteins (fold-change ≥ 2; p-value ≤ 0.05) between the strains. A total of 730 and 685 spots were visualised in the Bp MARAN and Bpmouse-adapted strains, respectively. Of the 730 spots (Bp MARAN as reference gel), 87 spots were differentially regulated (44 up- and 43 down-regulated). The identified proteins were classified as proteins related to metabolism, stress response, virulence, signal transduction, or adhesion. In comparison, it was found that those proteins related to adhesins, virulence factors and stress- response were up-regulated and could possibly explain the adaptation of the bacteria in the host. Investigating the differentially expressed proteins may provide better perspective of bacterial factors which aid survivability of B. pseudomallei in host.